İletken Polimer Kaplamanın Karbon Köpüğün Elektriksel Ve Yapısal Özellikleri Üzerine Etkisi - Sipahi, Melda (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, mezofaz zift bazlı karbon köpük üzerine anilinin elektropolimerleşme yöntemi ile kaplanması ve kaplamanın karbon köpüğün yapısı üzerine etkileri araştırılmıştır. Deneyler farklı monomer konsantrasyonları, çevrim sayıları ve tarama hızlarında gerçekleştirilmiştir. Elde edilen örneklerin yüzey özellikleri taramalı elektron mikroskobu ile, kimyasal bileşimi FTIR ölçümleri ile, elektriksel özellikleri ise elektrokimyasal impedans spektroskopisi ile analiz edilmiştir. Çalışma sonucunda anilin monomerinin karbon köpük üzerine kaplanması sağlanmıştır ve farklı proses şatlarında gerçekleştirilen deneylerin sonuçları irdelenmiştir.

Electropolymerization of aniline on mesophase pitch based carbon foam have been studied in order to evaluate the influence of conductive polymer coating on the properties of carbon foam. Studies were carried out at different monomer concentrations, cycle numbers and scan rates. The surface morphology of the coating was determined by scanning electron microscopy and chemical composition of the polymer was characterized by Fourier Transform-InfraRed reflectance measurements. Cyclic voltammetry and electrochemical impedance spectroscopy were used to investigate the electrochemical properties of resulting carbon foam samples. Electrochemical coating of aniline on carbon foam electrode is succeeded and the effects of process conditions changes are studied.
Influence Of Thin Conductive Polymer Coating On The Morphological And Electrical Properties Of Carbon Foam
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2006
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2006
Keywords: karbon köpük; karbon kompozitler; iletken polimer kaplama; elektrokimyasal kaplama; carbon foam; carbon composite; conductive polymer coating; electrochemical coating